Giving Form to the Formless: from the Kantian sublime to the debate between Rosalind Krauss and Georges Didi-Huberman - Feloj, Serena (Aesthetica Preprint, 2024)
In this text, I will ask whether an artistic representation of the sublime is possible from one of its essential characteristics: the absence of form. Beginning with the Kantian notion of formlessness and its theoretical implications, I would like to refer to Rosalind Krauss’s (1996) reading and the debate engaged in with Georges Didi-Huberman (1995). In this journey around formlessness I will make mention of the entry “formlessness” that Bataille publishes in Documents (Bataille 1929). The thesis that I would like to argue, taking a position in the debate, is that even in the experience of the sublime, which is entirely subjective and originates in formlessness, there emerges the purely human need to resort to form and representation.